Pharmacological effects of specialized pro-resolving mediators in sepsis-induced organ dysfunction: a narrative review - Sun, Shujun; Yang, Dong; Lv, Jing; Xia, Haifa; Mao, Zhangyan; Chen, Xiangdong; Gao, Yafen (Frontiers in Immunology, 2024)
Sepsis is a life-threatening syndrome of organ dysfunction, characterized by uncontrolled inflammatory response and immune dysregulation, often leading to multiple organ failure and even death. Specialized pro-resolving mediators (SPMs), which are typically thought to be formed via consecutive steps of oxidation of polyenoic fatty acids, have been shown to suppress inflammation and promote timely resolution of inflammation. They are mainly divided into four categories: lipoxins, resolvins, protectins, and maresins. The SPMs may improve the prognosis of sepsis by modulating the immune and inflammatory balance, thereby holding promise for clinical applications. However, their biosynthetic and pharmacological properties are very complex. Through a literature review, we aim to comprehensively elucidate the protective mechanisms of different SPMs in sepsis and its organ damage, in order to provide sufficient theoretical basis for the future clinical translation of SPMs.